Decoding Sentiment in Online Communication: A Social Media Analysis of Fashion Companies - Karolina Mania; Monika Jedynak; Aneta Kuźniarska; Karolina Woszczyna (European Management Studies)
Purpose: The aim of this article was to identify differences in the emotional tone of verbal messages published on the Facebook accounts of selected companies within the fashion industry, focusing on organizations with an active presence on this platform.